Pengaruh Budaya Organisasi dan Kepemimpinan terhadap Kinerja Pengurus Cabang Olahraga dan Prestasi Atlet KONI Riau - Satria, Deswita (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2018)
The purpose of this study is to analyze organizational culture and leadership of the sport branch Board and Athlete Performances and impact against KONI (Indonesian National Sport Committee) of Riau Province. The object of research is the Sport Branch Board members of KONI (Indonesian National Sport Committee) of Riau Province. Population in this study is the Sport Branch Board members of KONI of Riau province as many as 165, with a sample of 117 people, by using a formula Solvin. The type of data required in this research is primary data and secondary data. Primary data sources were obtained from the results of empirical research through deployment questionnaire to the Branch Board Sports, while the secondary data source authors were obtained in the form of ready-made include about organisational profile of KONI of Riau Province.  Data collection methods used were interviews and questionnaires. Data analysis tools used in the study was a multiple linear regression analysis.  Results from this study showed that: (1) There is a positive effect of the Cultural Organization (X1) on the performance variable (Y1) the coofficient 0,386 with sig = 0.002 ≤ 0,05; (2) there is a positive influence Leadership variable (X2) of the variable Cultural Organization (Y1) the coofficient 0,182 with sig = 0,038 ≤ 0,05; (3) there is a positive influence organizational culture variable (X1) to achievement athlete (Y2) the coefficient 0,252 with sig 0,002, 4). there is positive leadership variables (X2) on achievment athlete (Y2) the coefficient 0,287 with a value coofficient sig = 0,000 ≤ 0,05. there is a positive influence organizational culture variables (X1) to the achievement athlete (Y2) with sig = 0,000 ≤ 0,05. Cultural organizations are independent variables that influence is greater than the other independent variables. Coofficient determination or R-square is 79.04%, while 20.96% is influenced by other variables outside the research. Suggestions for further research are to find out other variables that have a greater influence on the performance of government policy, and the development of school sports.